Zero poverty campus program: Empowering student needs based on the zakat system / Hamdi Rahman Mohd Yaacob ... [et al.] - Mohd Yaacob, Hamdi Rahman; Md Noh, Abdul Munir; Arshad, Mohd Fawazie; Ali Hasan, Ahmad Rozaini; Fathil, Fathiah (2024)
The Campus Zero Poverty Program is an initiative at UiTM Perak Branch under the Zakat, Sedekah, and Wakaf Unit, aimed at achieving the goal of no poverty, which is the first of the 17 Sustainable Development Goals (SDGs) initiated by the United Nations. The mission of this program is to ensure that all diploma and degree students have sufficient educational financial resources to cover the minimum cost of educational needs for a semester. To achieve this mission, three objectives have been outlined. Firstly, establishing an inclusive zakat application system for needy students to ensure that every student in need has been given the opportunity to apply for zakat. Secondly, implement a fair zakat distribution method based on student individual financial needs. Thirdly, working on ensuring adequate zakat distribution rate compared to the minimum cost of educational financial needs of zakat recipients. The zakat needs calculation system is developed using a Google Sheet application that is automatically linked with Google Forms software as a medium for collecting application information. The individual zakat needs of applicants are automatically calculated using a specific formula to identify the budget deficit faced by the applicants by examining their financial shortcomings in covering the minimum learning costs for the current semester. Besides being used to determine the zakat distribution rate to recipients, the data obtained is also used to illustrate the level of campus poverty faced at UiTM Perak Branch in external zakat contribution applications. The performance indicator for the Campus Zero Poverty Program is measured by referring to the percentage of zakat funds collected for the c